A RARE CASE OF ECTOPIC LINGUAL THYROID WITH SUBCLINICAL HYPOTHYROIDISM - Teh, Kai Xuan; Ho, Jin Hui; Tee, Hwee Ching (Journal of the ASEAN Federation of Endocrine Societies, 2025)
INTRODUCTION Ectopic thyroid tissue may be found in locations other than the anterior neck region, and lingual thyroid accounts for 90% of the ectopic cases. It is an embryological aberration where the thyroid gland fails to descend from the foramen cecum to the lower part of the neck. Individuals with lingual thyroid are usually asymptomatic, but local obstructive symptoms may develop. Subclinical hypothyroidism is a common manifestation in patients with an ectopic lingual thyroid without a co-existing orthotopic thyroid gland. We present a case of ectopic lingual thyroid with subclinical hypothyroidism. METHODOLOGY A 68-year-old female presented with progressive voice changes for many years, associated with intermittent shortness of breath upon lying flat. Physical examination and transnasal scope showed a mass at the base of the tongue pushing on the epiglottis with oedematous bilateral arytenoids. Tracheostomy, direct laryngoscopy and tele-bronchoscopy were performed, and tumour fluid for cytology was negative for malignant cells. MRI of the neck revealed an ectopic lingual thyroid with nodular goitre and haemorrhagic cystic component causing oropharyngeal luminal narrowing, with absence of orthotopic thyroid gland. She is clinically euthyroid but biochemically subclinical hypothyroidism (TSH 11.87 uIU/mL, FT4 13.07 pmol/L). Anti-TPO antibodies were negative; a neck ultrasound showed no normal thyroid tissue in the anterior neck. Thyroxine hormone replacement commenced, and her TFT levels normalized 4 months later. Repeat neck CT showed no reduction in the size of the lingual thyroid. However, she declined surgical intervention. CONCLUSION Lingual thyroid is extremely rare but remains an important differential for patients presenting with a mass at the tongue base. Treatment with thyroxine should be initiated to prevent hypothyroidism and progressive growth of the ectopic tissue. Surgical intervention is indicated when the patient presents with severe respiratory tract obstruction, limited size-reduction despite thyroxine replacement or malignancy.